A Model of Online Food Delivery System Services and Restaurant Performance: A Case Study of China - Shiqiang Yan; Sidah Idrisb; Syarifah Hanum Ali (Global business & finance review, 2024)
Purpose: Through the lens of business performance theory, this study examines the effect of online food delivery system services on restaurant performance by analyzing the performance of restaurants engaged in takeaway services. The moderating effects of restaurant attributes on restaurant performance are also investigated. Design/methodology/approach: This research applies a positivist paradigm where a quantitative approach was selected to gather the information from the respondents based on the established sample size through G-POWER software. By applying the judgement sampling technique, the study seeks answers from the respondents through non-probability sampling. Using the software SmartPLS 3.3.3, this study analyzed 220 completed responses using the PLS-SEM approach to reach the research objectives. Findings: The findings suggested that the basic services and click-through promotion service directly and positively affected restaurant performance. The discount service has no significant influence on the restaurant performance. The study confirms that size shown a positive interaction with click-through promotion service in relation to restaurant performance, whereas the variable of price of main dishes demonstrated a negative interaction with click-through promotion service in relation to restaurant performance. There is no substantial moderating influence of age. Research limitations/implications: The current study is limited to the geographical area, of Baise, Guangxi China. Therefore, generalizability and gain a better knowledge of the overall context is limited. Additionally, due to the single time period of data collection, it may not represent the long-term takeout business operation of catering businesses. Originality/value: The research model is valid in explaining the impact of online food delivery system services on restaurant performance. In this light, understanding these influencing relationships in this study will provide valuable insights into the operation of a takeout catering enterprise. These would also benefit the related government agencies, restaurant owners or managers, and the researchers.